Community participation on solid waste segregation through recycling programmes in Putrajaya - Abdul Malik, Nur Khaliesah; Abdullah, Sabrina Ho; Abd Manaf, Latifah (Elsevier, 2015)
Recycling programmes have been conducted by various stakeholders including Government sector and private sector to reduce waste generation from being disposed into the landfill. The objectives of this study was identifying the correlation between the community participation in recycling programme and community attitude and their knowledge on solid waste segregation. The fully structured questionnaires were filled in by 382 respondents through random sampling. The result shows that there was a weak and positive correlation between community participation in recycling programme with community attitude on solid waste segregation, r = 0.343; and community knowledge on solid waste segregation, r = 0.251. Policy review by Government is highly recommended to identify the factors that can influence more community participation in recycling programmes